Effect of ZnO Dopant on TiO2 on Simultaneous Decrease of Phenol, Pb(II) and COD using Photocatalysis Method - Steffita Rahayuning Purbandini; Abdul Haris (Jurnal Kimia Sains dan Aplikasi, 2018)
A study entitled the effect of ZnO dopant on TiO2 on the decrease in phenol, Pb (II), and COD levels simultaneously has been performed. This study aims to synthesize TiO2 and TiO2/ZnO composites, to determine the character of TiO2/ZnO, and to measure the activity of TiO2/ZnO and TiO2 composites on the degradation of phenol wastes, decrease of Pb (II) and COD concentration. The method used was photocatalysis with TiO2 and with TiO2/ZnO. The characterization of TiO2/ZnO composites was analyzed using SEM-EDS. Photocatalysis was measured using a time variable of 1-4 hours with UV light. In photocatalysis using TiO2/ZnO composite, it was found that the maximum reduction of phenol, Pb (II), and COD concentrations occurred at the time of photocatalysis for 4 hours.